2021
DOI: 10.1021/acs.jpclett.1c01306
|View full text |Cite
|
Sign up to set email alerts
|

Non-energetic, Low-Temperature Formation of Cα-Glycyl Radical, a Potential Interstellar Precursor of Natural Amino Acids

Abstract: The reaction of H atoms with glycine was investigated at 3.1 K in para-H 2 , a quantum-solid host. The reaction was followed by IR spectroscopy, with the spectral analysis aided by quantum chemical computations. Comparison of the experimental IR spectrum with computed anharmonic frequencies and intensities proved that, regardless of the reactant glycine conformation, C α -glycyl radical is formed in an H-atom-abstraction process with great selectivity. The product of the second H-atom abstraction, iminoacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…Furthermore, our results corroborate with those of Ioppolo 48 et al and Joshi 79 et al , who showed that glycine by non-energetic glycine mechanisms can be formed in the presence of H atoms in dark clouds and in a similar manner very recently, Tarczay 80 et al have shown that “natural α-amino acids can be formed from glycine via the Cα-glycyl radical by non-energetic mechanisms in the solid phase of the interstellar medium. Moreover, our paper highlights the complementarity between gas-phase interstellar chemistry – a reaction pathway studied by Rimola et al in ref.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, our results corroborate with those of Ioppolo 48 et al and Joshi 79 et al , who showed that glycine by non-energetic glycine mechanisms can be formed in the presence of H atoms in dark clouds and in a similar manner very recently, Tarczay 80 et al have shown that “natural α-amino acids can be formed from glycine via the Cα-glycyl radical by non-energetic mechanisms in the solid phase of the interstellar medium. Moreover, our paper highlights the complementarity between gas-phase interstellar chemistry – a reaction pathway studied by Rimola et al in ref.…”
Section: Resultssupporting
confidence: 92%
“…We have investigated reactions of H atoms with astronomically relevant species such as methanol CH 3 OH, [ 62 ] formamide HC(O)NH 2 , [ 80 ] methyl formate HC(O)OCH 3, [ 57 ] acetamide CH 3 C(O)NH 2 , [ 81 ] acetic acid CH 3 C(O)OH, [ 82 ] glycine NH 2 CH 2 C(O)OH, [ 83 ] methyl amine CH 3 NH 2 , [ 84 ] and N‐methyl formamide HC(O)NHCH 3 [ 85 ] ; as discussed previously, these species are building blocks of peptides, as illustrated in Figure 5. The UV/IR irradiated matrix was typically maintained in darkness for more than 10 h to facilitate H‐atom tunneling reactions.…”
Section: Reactions Of H Atoms With Astrochemically Relevant Speciesmentioning
confidence: 99%
“…[ 109,110 ] In collaboration with Tarczay's group in Hungary, we investigated reaction H + NH 2 CH 2 C(O)OH. [ 83 ] The spectrum of deposited glycine in p ‐H 2 reveals three isomers, Ip (0.0), IIn (3.8), and IIIn (7.2); values in parentheses represent the relative energies in kJ mol −1 with respect to most stable isomer Ip. UV/IR irradiation of Cl 2 ‐doped NH 2 CH 2 C(O)OH/ p ‐H 2 matrices formed C α ‐glycyl radical, H 2 N•CHC(O)OH (referred to as In CH ) after H‐abstraction on the methylene moiety of Ip; lines of In CH were unambiguously assigned according to quantum‐chemical computations.…”
Section: Reactions Of H Atoms With Astrochemically Relevant Speciesmentioning
confidence: 99%
“…Among the possible molecules that can act as catalysts in these reactions, polyaromatic hydrocarbons (PAHs) 8−12 and small organic molecules 13,14 were investigated by theoretical and experimental methods. The role of PAHs in H 2 formation can be especially important in photon-dominated regions (PDRs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although H 2 is the smallest and the most abundant molecule of the interstellar medium (ISM), its formation in the present universe is still not fully understood. Due to the low-pressure conditions in the ISM, and due to the lack of a dipole moment for H 2 , its gas-phase formation rate from H atoms both by three-body collision (eq ) and by radiative association (eq ) mechanisms is practically zero. …”
Section: Introductionmentioning
confidence: 99%